Worker Commitment and Establishment Performance - John T. Addison; Paulino Teixeira (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Using a cross section of matched data from the employee and management questionnaires of the European Company Survey, this paper investigates the determinants of worker commitment and the potential contribution of commitment to establishment performance. An index of worker commitment is constructed from employer perceptions of the motivation of workers and their retention and absenteeism propensities, while the determinants of commitment are fashioned from observations taken from the worker representation side ordered along dimensions such as perceived organizational trust and involvement. The commitment index is then linked to establishment performance outcomes. Key findings from the commitment equation are the positive role of trust in management, the quality of information exchanged, and the degree of worker representation influence in respect of major decisions taken by management. In turn, commitment emerges as a key correlate of establishment financial performance and labor productivity growth. Our supplemental sensitivity analysis is supportive of the interpretation of commitment as a driver of performance.
Keywords: J20; J50; 330; commitment; type of workplace representation; financial performance; labor productivity growth; European Company Survey